CLINICAL CASES OF ANALYZING OBSERVATIONS OF COMBINED CONGENITAL MALFORMATIONS OF THE BRAIN AND VISION IN NEWBORNS (World Bulletin of Public Health, 2024)
The present study is aimed at investigating clinical and diagnostic features of combined congenital malformations of the brain and vision in children